Human Organ Trafficking as a Health Crime: An Analysis of Indonesian Criminal Law - Wayan Santoso (Indonesian Journal of Global Health Research, 2026)
Human organ trafficking has emerged as a serious challenge at the intersection of health law, criminal law, and human rights in Indonesia. Despite the prohibition of organ commercialization under national legislation, the illicit trade in human organs continues to occur, indicating limitations in the existing legal framework and enforcement mechanisms. Aims: This study aims to analyze human organ trafficking as a health-related crime within the Indonesian criminal law system and to critically assess the adequacy of current legal regulations in addressing its complex medical, ethical, and human rights dimensions. The research employs an analytical–critical normative juridical approach. Relevant statutory provisions, including health law, criminal law, and human trafficking legislation, are examined through statutory, conceptual, and limited comparative approaches. The study relies on primary legal materials, scholarly literature, and international legal instruments, which are analyzed using qualitative legal analysis. The findings reveal that Indonesian law addresses organ trafficking through a fragmented regulatory framework, resulting in legal ambiguity and inconsistent enforcement. The absence of a distinct criminal offense for organ trafficking complicates the determination of criminal liability and often leads to disproportionate punishment of vulnerable donors while inadequately targeting organized networks and professional actors. Additionally, victim protection mechanisms, particularly in terms of medical aftercare and legal support, remain insufficient. The study concludes that comprehensive criminal policy reform is necessary to effectively address human organ trafficking in Indonesia. Explicit recognition of organ trafficking as a distinct health-related crime, integration of health law safeguards, and adoption of a victim-centered approach are essential to ensure legal certainty, proportional justice, and alignment with international human rights standards.